"King Lear" and the Absolute Tragedy: Shakespeare, von Balthasar, and Marion on Love, Sacrifice, and Forgiveness - Grzegorzewska, Małgorzata (Religion & literature, 2024)
Against the absurdist interpretations of King Lear, the author analyzes this play as a specifically Christian tragedy. The focus on Christian notions of self-sacrifice and forgiving love, which is apparent in the play's thematic or verbal analogies with the Bible, Christian liturgy, and fine arts, points to the mystery of the cross. The play is read in the light of Hans Urs von Balthasar's understanding of the tragic and Jean-Luc Marion's idea of a superabundant gift, encapsulated in the phenomena of sacrifice and forgiveness. Both the main plot and the subplot of King Lear illustrate the underlying correspondence between sacrifice and forgiveness as being ways of revealing the gift ignored or wasted by the receiver. For example, Shakespeare's portrayal of Edgar's folly and his journey with Gloucester to Dover is linked to the sacrifice of Isaac as being analogous to the crucifixion, and the death of Cordelia is read here as a Trinitarian passion scene.